EVALUASI PROGRAM ENGLISH CLUB DI INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS - M. Sabiqul Huda (CV. ADIBA AISHA AMIRA, 2022)
The aims of this study are (1) to determine the needs of the English Club, (2) to review the English Club's human resources and infrastructure, (3) to evaluate the implementation of the English Club, and (4) to examine the results of the English Club program. The method used in this study is a descriptive qualitative method with the CIPP model. The results of this study are first, how the English Club can become a forum for IAIS Sambas students to have good English skills and this can be seen from the purpose of the establishment of the English Club itself. Then, the English Club already has a quite good infrastructure, but for teaching staff it uses non-experts. Next, at the implementation level, it has been carried out quite well, although there are still obstacles. Finally, the program is successful for active members who have a good base of English skills. But for members who are not active in English, this program is not much help.